A Study on Modelling of Bivariate Competing Risks with Archimedean Copulas - , Cigdem Topcu Guloksuz (Archives of Current Research International, 2021)
In this study we consider Archimedean copula functions to obtain estimates of cause-specific distribution functions in bivariate competing risks set up. We assume that two failure times of the same group are dependent and this dependency can be modeled by an Archimedean copula. Based on the Archimedean copula which gives best fit to the competing risk data with independent censoring we obtain the estimates of cause specific sub distributions.